Allergy Frontiers: Therapy and Prevention - Pawankar, Ruby.; Holgate, Stephen T.; Rosenwasser, Lanny J.; SpringerLink (Online service) (Tokyo : Springer Japan, 2010)
The prevalence of asthma and other allergic diseases is on the rise worldwide, with a marked impact on quality of life and socioeconomics. Allergy Frontiers comprises six volumes, each dedicated to a specific aspect of the disease to reflect the multidisciplinary character of the field and its explosive growth. Included are reviews by world-renowned scientists from Europe, North and South America, Australia, Japan, other parts of Asia, and South Africa. The fifth volume is dedicated to therapy and prevention of allergies, including pharmacotherapy and allergen-specific immunotherapy, with novel aspects and special considerations for particular groups such as children, the elderly, and pregnant women. This book serves as a valuable tool for scientists and as a practical guide for clinicians working in the fields of allergy, asthma, and immunology.
Therapy and Prevention of Allergies -- Allergen Avoidance and Prevention of Allergy -- Pharmacotherapy of Allergic Rhinitis -- Antihistamines in Rhinitis and Asthma -- Antiallergic and Vasoactive Drugs for Allergic Rhinitis -- Antileukotrienes in Asthma and Rhinitis -- Mechanisms of Action of ?2 Adrenoceptor Agonists -- Alkylxanthines and Phosphodiesterase 4 Inhibitors for Allergic Diseases -- Glucocorticoid Insensitive Asthma -- Recalcitrant Asthma -- Mechanisms and Management of Exercise-Induced Bronchoconstriction -- Use of Theophylline and Sodium Cromoglycate in Adult Asthma -- New Insights into Allergen-Specific Immunotherapy in Rhinitis and Asthma -- Sublingual Immunotherapy in Allergic Rhinitis and Asthma -- Anti-IgE in Allergic Airway Diseases: Indications and Applications -- Drug Delivery Devices and Propellants -- Update on the Management of Atopic Dermatitis/Eczema -- Immunosuppressants as Treatment for Atopic Dermatitis -- Management of Anaphylaxis -- Anaphylaxis: Are Regulatory T Cells the Target of Venom Immunotherapy? -- Food Allergy: Opportunities and Challenges in the Clinical Practice of Allergy and Immunology -- Early Immunological Influences on Asthma Development: Opportunities for Early Intervention -- Asthma and Allergy in Childhood: Prediction and Early Diagnosis -- Early Interventions in Allergic Diseases -- Birth Cohort Studies for the Prevention of Allergy: New Perspectives Where Do We Go from Now? -- Novel Immunomodulatory Strategies for the Prevention of Atopy and Asthma -- Recombinant Allergens for Therapy and Prevention: Molecular Design and Delivery of Allergy Vaccines -- Prevention of Allergic Diseases -- Emerging Nonsteroidal Anti-Inflammatory Therapies Targeting Specific Mechanisms in Asthma and Allergy -- Special Considerations in Children, Elderly and Pregnancy -- Asthma and Rhinitis in Pregnancy -- Asthma in the Elderly -- The Natural History of Childhood Asthma -- The Wheezing Infant and Young Child -- Acute Severe Asthma in Children -- Best Estimates of Asthma Control in Children -- Risk-Benefit of Asthma Therapy in Children: Topical Corticosteroids -- Risk-Benefit of Asthma Therapy in Children: Nonsteroidal Anti-Inflammatory Drugs -- The Role of Influenza Vaccination in Asthmatic Children -- Treatment of Infants with Atopic Dermatitis -- Diagnosing Food Allergy in Children -- Diagnosis and Treatment of Latex Allergy -- New Aspects of Peanut and Tree Nut Allergy -- Allergic Fungal Sinusitis: Controversy and Evolution of Understanding with Therapeutic Implications -- Immunomodulatory Role of Bacillus Calmette-Guérin in the Prevention and Therapy of Allergy and Asthma -- Use of Theophylline and Sodium Cromoglycate in Pediatric Asthma -- Antibody Deficiency Syndromes (Including Diagnosis and Treatment).
Keywords: Medicine; Immunology; Allergy; Internal medicine; Medicine & Public Health; Allergology; Immunology; Internal Medicine